EVALUATION OF TARGET PRODUCTION ATTAINMENT FOR HEAVY EQUIPMENT UTILIZING QUEUEING THEORY IN OVERBURDEN REMOVAL AT PIT B PT XYZ - Tri Hartati, Linda
PT XYZ is one of the coal mining companies in Indonesia which is a supplier of coal for PLTU needs. The applied mining system is an open pit mining system using a combination of a backhoe as a digging tool and a dump truck as a means of conveyance. One of the important activities in open pit mining operations is the excavation-loading and hauling of overburden. Therefore, this activity must run optimally so that the resulting production is in accordance with the production target so that the progress of the mine can proceed according to the plans that have been made. In this study an evaluation will be carried out regarding the achievement of production targets by reviewing the productivity of the heavy equipment used and then compared with the optimal capacity of the tool. Queuing theory will be used as a supporting theory in selecting the number of tools and the production capacity of the tools. In this queuing cycle system it is assumed that there are only four service nodes, namely loading and unloading of overburden at the work front (loading), transporting overburden to the waste dump (hauling), dumping of overburden (dumping), and returning to the work front (returning). ). Total monthly production before the evaluation was 84,573 BCM with 2 passes, this production was still far from the production target of 130,000 BCM. However, after adding the number of passes to 6 times, the resulting total production can reach 170,312 BCM.